Representation of adverse childhood experiences is associated with lower public stigma towards people who use drugs: an exploratory experimental study. (4th May 2021) - Sumnall, Harry R.; Hamilton, Ian; Atkinson, Amanda M.; Montgomery, Catharine; Gage, Suzanne H.
Abstract: Background: Stigmatising attitudes towards people who use drugs are pervasive amongst the public. We investigated whether public stigma was affected by presentation of a history of adversity, and how substance use was described. Methods: A cross-sectional online study using a convenience sample, with a randomised 2 × 2 × 2 factorial design. Participants read one of eight randomly presented vignettes that described a fictional case history of substance use. In each vignette, the gender of the subject (male or female), description of the subject's substance use ('addict' vs substance use disorder), and life history ('tough life' vs description of four adverse childhood experiences (ACEs)) were varied. Participants then completed an adapted version of the attribution questionnaire (AQ-9), which assessed stigmatising beliefs. Results: Data were obtained from 502 participants (53.0% female; mean age 36.5 ± 13.5 years). There was a significant effect of life history on AQ-9 scores ( p = .012), and presentation of ACEs was associated with lower stigmatising attitudes. Conclusion: Our findings suggest that describing the life histories of people who have experienced problems with substances may lead to less stigmatising public attitudes. Further research should explore the best ways to utilise this information to develop public-targeted anti-stigma interventions.